PENGARUH PERCEIVED ORGANIZATIONAL SUPPORT, KNOWLEDGE MANAGEMENT DAN TRUST BUILDING TERHADAP KINERJA PADA PERSONIL DIREKTORAT INTELKAM POLDA SULTRA - Ruslan Aristo; Alida Palilati; Asrip Putera (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2022)
This study aims to: 1) The simultaneous influence of Perceived Organizational Support, knowledge management and Trust Building simultaneously on the Personnel Performance of the Directorate of Intelligence and Security at the Southeast Sulawesi Police, 2) find out that Perceived Organizational Support has a positive and significant effect on the Personnel Performance of the Southeast Sulawesi Police Intelligence and Security Directorate. , 3) knowing that knowledge management has a positive and significant effect on the Personnel Performance of the Intelligence and Security Directorate of the Southeast Sulawesi Police, 4) knowing that the Tust Building has a positive and significant effect on the Personnel Performance of the Directorate of Intelligence and Security of the Southeast Sulawesi Police.The object of this research is the Directorate of Intelligence and Security of the Southeast Sulawesi Police with a total population of 100 personnel. Determination of the sample sampling technique is done by census. The research data was collected using a questionnaire, the research data was analyzed using SPSS version 22 to determine the results of the regression analysis of the influence of the independent variable on the dependent variable.The results of the study: 1) simultaneously and positively perceived organizational support, knowledge management, and test building affect the performance of members of the Directorate of Intelkam Polda Sultra, 2) Perceived organizational support has a positive and significant effect on the performance of members of the Directorate of Intelkam Polda Sultra, 3) Knowledge management has an effect positive and significant impact on police generic performance, and 4) Test building has a positive and significant effect on the performance of members of the Directorate of Intelligence and Security for the Regional Police of Southeast Sulawesi